Ecological Assessment of a Sediment By‐pass Tunnel on a Receiving Stream in Switzerland. (22nd March 2017) - Martín, E. J.; Doering, M.; Robinson, C. T.
Abstract: Reservoir siltation is a major problem worldwide, decreasing reservoir storage capacity, trapping entrained sediment, and altering the natural sediment regime. Sediment By‐pass Tunnels (SBTs) are used to connect reservoirs with downstream receiving waters during high flows to reduce sediment accumulation in the reservoir. When operating, large volumes of sediment‐laden waters are released into the receiving river for short periods of time (h). The aim of this study was to assess the impact of SBT events on the downstream riverine ecosystem. We measured physico‐chemical properties, sediment respiration, periphyton biomass and chlorophyll‐a, and macroinvertebrate assemblages along a 5‐km stretch of river during the first two years of SBT operation. During the study, five major SBT events occurred. Few changes were found in physico‐chemical properties, mainly due to the input of tributaries entering the system. Results showed a clear reduction in sediment respiration, an indicator of ecosystem metabolism, especially after large SBT events. Periphyton levels and macroinvertebrate density/richness also decreased after SBT events. A non‐metric multidimensional scaling distinguished both temporal and spatial shifts in macroinvertebrate assemblages after SBT events, being related to downstream distance and SBT event magnitude. In summary, SBT events acted as a pulse disturbance, similarly to natural floods, followed by recovery of measured ecosystem indicators. Sediment By‐pass Tunnel events can enhance sediment and flow connectivity, although the magnitude and frequency of operations should be controlled to prevent catastrophic disturbances. Copyright © 2017 John Wiley & Sons, Ltd.